Cut, shape, assemble : easy woodworking crafts for small spaces - Paterson, Boo (Countryman Press, an imprint of W.W. Norton & Company, 2024)
"Step-by-step projects for all skill levels to spruce up your home, from bookends to breakfast trays to birdhouses. With the right tools, guidance, and attitude, anyone can create beautiful and useful home goods from wood. In Cut, Shape, Assemble, award-winning artist Boo Paterson empowers you to craft with confidence and embark on your own creative journey. With information on tools and materials, clear instructions, full-color photography, and one-of-a-kind, hand-drawn blueprints, she guides you through easy-to-make projects that can be pulled together on the floor of a small apartment. All the designs in this book are stylish and modern, with everything a homeowner needs, like a knife block, plant stand, and even a table! Cutting boards, bookends, and serving platters make for wonderful additions to your home or great gifts for friends and family. Whether you’re a woodworking enthusiast, hobbyist crafter, or complete newcomer, this encouraging guide will inspire you to elevate your living space, your creativity, and your confidence as you experience the joy of making something of your own out of wood.